Was There Dual Authorship in Greek Historiography? A Critical Overview of the Epigraphic and Literary Evidence from Aristotle to Pamphile of Epidaurus - Schropp, Jack W. G. (Histos, 2023)
This paper discusses jointly written works in ancient literature. Although this topic has received little attention, there is sufficient evidence, particularly from epigraphic sources, that informs us about dual authorship in Greek historiography. The main aim of this paper is to present those examples and to explore what influence dual authorship might have had on the content of those historiographical works. In this context, it will also be discussed why this phenomenon is encountered only sporadically in antiquity.